The Value of Honesty in Academic Work - Flores Morales, Jorge Alberto (2018)
Intellectual honesty in academic work is not only a value but also a human quality as such. The lack of honesty conveyed in plagiarism harms not only the individual as a professional but also the academic community, which expects seriousness and truthfulness in every paper submitted. When this value is transgressed the door is opened to the rise of anti-values such as arrogance, laziness and falsehood. Therefore, we must make the effort to demand serious  academic work by means of the appropriate tools available today.